Building Competitiveness for Semarang City Tourism Marketing Elements - Andi - Setiawan; Rustono - Rustono; Sri - Wahyuni; Subandi - Subandi (Politeknik Negeri Semarang, 2019)
Potential foreign exchange outstanding tourism, the tourism industry Semarang demand should continue to improve to capture the potential of becoming a source of opinions. Industry conditions pariwisatan in Semarang require a marketing development model that encourages stakeholders in the field of tourism. Semarang City Tourism marketing requires an analysis of the competitiveness model approach marketing elements. Referring to the phenomenon above, this study proposes further research problems of modeling Design Marketing able to increase customer satisfaction (rating) in Semarang on an ongoing basis. The sampling technique used in this study was accidental sampling method in this case that travelers in Semarang and surrounding areas. As for the amount of sample is 103 samples. This research technique using two approaches: 1) .Confirmatory factor analysis, the Structural Equation Modeling (SEM); and 2). Regression Weight on Structural Equation Modeling (SEM). Modeling in this study is expected to capture potential foreign exchange earnings, revenues, jobs and the development of tourism in the city of Semarang. It required an increase in the value of customers (customer value), so that the potential it can achieve its full potential. In addition, the tourism industry and stakeholders can take advantage of empirical findings of this research.